The control of red colour by a family of MYB transcription factors in octoploid strawberry (Fragaria × ananassa) fruits. Issue 5 (12th December 2019) - Wang, Hua; Zhang, Hui; Yang, Yuan; Li, Maofu; Zhang, Yuntao; Liu, Jiashen; Dong, Jing; Li, Jie; Butelli, Eugenio; Xue, Zhen; Wang, Aimin; Wang, Guixia; et al.
Summary: Octoploid strawberry ( Fragaria × ananassa Duch.) is a model plant for research and one of the most important non‐climacteric fruit crops throughout the world. The associations between regulatory networks and metabolite composition were explored for one of the most critical agricultural properties in octoploid strawberry, fruit colour. Differences in the levels of flavonoids are due to the differences in the expression of structural and regulatory genes involved in flavonoid biosynthesis. The molecular mechanisms underlying differences in fruit colour were compared between red and white octoploid strawberry varieties. FaMYB genes had combinatorial effects in determining the red colour of fruit through the regulation of flavonoid biosynthesis in response to the increase in endogenous ABA at the final stage of fruit development. Analysis of alleles of FaMYB10 and FaMYB1 in red and white strawberry varieties led to the discovery of a white‐specific variant allele of FaMYB10, FaMYB10‐2 . Its coding sequence possessed an ACTTATAC insertion in the genomic region encoding the C‐terminus of the protein. This insertion introduced a predicted premature termination codon, which suggested the loss of intact FaMYB10 protein playing a critical role in the loss of red colour in white octoploid strawberry .